Pendampingan Usahanya Anyaman Daun Panda di Desa Mbatakapidu dalam Penyusunan Harga Pokok Produksi - Linda R. K. Yowi; Siti Suryani; Alliny N. R. Hutar; Vindya D. Adindarena; Lusianus Heronimus Sinyo Kelen (Universitas Majalengka, 2021)
The problem related to the low level of Micro, Small and Medium Enterprises (MSMEs) in determining the cost of production in business financial management is one of the problems that often occur in the pandan leaf weaving business in Mbatakapidu Village, Waingapu City District, East Sumba Regency in East Nusa Tenggara Province (NTT). Therefore, with the assistance of MSMEs in compiling and making the cost of production in three stages, namely: first, preparation and planning. Second, implementation, and third, evaluation of the community service program (PKM), the results obtained are PKM, namely business owners are increasingly aware of the importance of calculating and determining the cost of production of their business. This activity also takes place in collaboration between lecturers, students, the Mbatakapidu Village government, and the owner of the pandan leaf weaving business.